2022
DOI: 10.1097/jom.0000000000002488
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders and Suicidal Behaviors Among Provincial Correctional Workers

Abstract: Objective: We examined the prevalence ofmental health disorders and suicidal behaviors (ideation, planning, and attempts) among a sample of provincial correctional workers in Manitoba. Methods: Self-reported mental health data from a survey on correctional worker mental health and well-being were analyzed for 491 correctional workers. Results: Over half (57%) of respondents screened positive for mental health disorder, most commonly major depressive disorder, and over one-third of respondents (37%) screened po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
9
0
3
Order By: Relevance
“…Again, a high prevalence of problematic alcohol use was noted among those with past-year suicide ideation (18.0%), as well as lifetime and past-year suicide plans (23.0% and 6.6%, respectively). Taking the starting point from previous scholarship, which illustrates how correctional workers have a high prevalence of mental health disorders and suicide behaviours (Ricciardelli, McKendy, Jamshidi, et al, 2022), our research reveals how mental health disorders were 2021) also found that some correctional workers experiencing suicide thoughts and behaviours would seek help from their family doctors, a psychologist, or Employee Assistance Program (EAP), but the lack of perceived organizational supports and recognition of the issues by the employers also hindered the treatment and help-seeking process. This is an important consideration for future research, as more studies are needed to unpack the relationships between substance misuse and suicide behaviours, and the other organizational factors (both protective and aggravating) that may be shaping these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Again, a high prevalence of problematic alcohol use was noted among those with past-year suicide ideation (18.0%), as well as lifetime and past-year suicide plans (23.0% and 6.6%, respectively). Taking the starting point from previous scholarship, which illustrates how correctional workers have a high prevalence of mental health disorders and suicide behaviours (Ricciardelli, McKendy, Jamshidi, et al, 2022), our research reveals how mental health disorders were 2021) also found that some correctional workers experiencing suicide thoughts and behaviours would seek help from their family doctors, a psychologist, or Employee Assistance Program (EAP), but the lack of perceived organizational supports and recognition of the issues by the employers also hindered the treatment and help-seeking process. This is an important consideration for future research, as more studies are needed to unpack the relationships between substance misuse and suicide behaviours, and the other organizational factors (both protective and aggravating) that may be shaping these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, correctional workers routinely experience exposure to potentially psychologically traumatic events (PPTEs), referring to operational stressors unique to the correctional or public safety environment that can be psychologically traumatic (i.e., prisoner violence, threats, self-injury, suicide attempts, and deaths) or events similar to those experienced by the general population (Carleton et al, 2020; Ricciardelli, Mitchell, Taillieu, et al, 2022). Such occupational strains and potentially psychologically traumatic exposures have been found to produce problematic mental health outcomes, including alcohol use disorder and its associated symptoms, coping mechanisms, and behaviours (Konyk et al, 2021; Ricciardelli, McKendy, Jamshidi, et al, 2022; Ricciardelli, Mitchell, Taillieu, et al, 2022).…”
Section: Mental Health Disorder Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Over half (57%) of respondents screened positive for mental health disorder, most commonly major depressive disorder, and over one-third of respondents (37%) screened positive for more than one disorder. Positive mental health screens for all mental health disorders were associated with statistically significantly increased odds of lifetime suicidal ideation, and positive screens for most disorders were associated with past-year suicidal ideation [28].…”
Section: Correctional Facilities and Correctional Treatment -Internat...mentioning
confidence: 91%